Modelling and predicting fatigue crack growth behaviour in weld induced residual stress fields - Servetti, Guido (Cranfield University, 2011)
In the last few decades, new design concepts and manufacture processes have been developed in order to reduce the maintenance and manufacturing costs, and structural weight of aircraft components. The integral metallic structure with welding processes is one of the most promising solutions. The exclusion of fasteners and overlapping joints in the airframe reduces the costs, the weight, and eliminates stress concentrations near the holes. The research and development of welding processes for large civil aircraft is in the early stages, thus assessment of their impact on damage tolerance (DT) design must be carried out before the technology can be applied for large civil aircraft. Cont/d.